Development of a VII-enabled prototype intersection collision warning system. (24th September 2009) - Nekoui, Mohammad; Ni, Daiheng; Pishro-Nik, Hossein; Prasad, Richa; Kanjee, Mohammed; Zhu, Hui; Nguyen, Thai
This paper presents the design of a prototype intersection collision warning system based on Vehicle Infrastructure Integration (VII). This system involves Roadside Equipment (RSE) at an intersection and several units of On-Board Equipment (OBE), each in a moving vehicle. When an equipped vehicle approaches the intersection, its OBE queries the remaining time before the light turns red from the RSE which is synchronised with the intersection signal. Combining its own speed and position, the OBE determines the likelihood of running the red light. In case of such a hazard, the OBE warns its driver and notifies other OBEs wirelessly.